(untitled) (International Journal of Studies in Nursing, 2019)
Background: The Professional Quality of Life scale is commonly used to measure Burnout, Secondary Traumatic Stress, and Compassion Satisfaction in nurses despite a lack of research regarding its psychometric properties in this population. This study evaluates the reliability and validity of the ProQOL version 5 in nurses. Methods: Chronbach’s alpha was used to assess reliability and Confirmatory Factor Analysis was used to test the validity of the three factor structure. Results: Reliability of the Burnout subscale is poor in nurses (α=.53). Confirmatory Factor Analysis revealed the tool’s three factor structure to not be valid in the nursing population (p<.001). Discussion: Despite being widely used, the ProQOL is not a valid or reliable tool in the nursing population. Recommendations are provided for creating a new tool to measure Burnout, Secondary Traumatic Stress and Compassion Satisfaction in nurses. Contribution of the Paper: What is already known about the topic: Burnout, Secondary Traumatic Stress and Compassion Satisfaction are important to study in the nursing population since these constructs can affect job performance and patient safety. By assessing nurses’ Burnout, Secondary Traumatic Stress and Compassion Satisfaction, targeted interventions can be created to enhance work efficiency and enjoyment, thereby improving nurse job satisfaction, nurse retention and patient outcomes. What this paper adds: Despite being commonly used in the nursing population, the ProQOL is not a valid or reliable tool for measuring Burnout, Secondary Traumatic Stress and Compassion Satisfaction in nurses. A new tool for measuring Burnout, Secondary Traumatic Stress and Compassion Satisfaction in nurses is needed.